Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) Sửa đề
\(x^4+2x^3+x^2\)
\(=\left(x^4+x^3\right)+\left(x^3+x^2\right)\)
\(=x^3\left(x+1\right)+x^2\left(x+1\right)\)
\(=\left(x+1\right)\left(x^3+x^2\right)\)
\(=\left(x+1\right).x^2\left(x+1\right)\)
\(=x^2\left(x+1\right)^2\)
b) \(x^3-x+3x^2y+3xy^2+y^3-y\)
\(=\left(x^3+3x^2y+3xy^2+y^3\right)-\left(x+y\right)\)
\(=\left(x+y\right)^3-\left(x+y\right)\)
\(=\left(x+y\right)\left[\left(x+y\right)^2-1\right]\)
\(=\left(x+y\right)\left(x+y-1\right)\left(x+y+1\right)\)
c) \(5x^2-10xy+5y^2-20z^2\)
\(=5\left(x^2-2xy+y^2-4z^2\right)\)
\(=5\left[\left(x-y\right)^2-\left(2z\right)^2\right]\)
\(=5\left(x-y-2z\right)\left(x-y+2z\right)\)
a,\(\frac{1}{5}x^2y\left(15xy^2-5y+3xy\right)=3x^3y^3-x^2y^2+\frac{3}{5}x^3y^2\)
b,\(5x^3-5x=5x\left(x^2-1\right)=5x\left(x-1\right)\left(x+1\right)\)
c, \(3x^2+5y-3xy-5x=3x\left(x-y\right)-5\left(x-y\right)\)
\(=\left(3x-5\right)\left(x-y\right)\)
1) 1/5x2y( 15xy2 - 5y + 3xy ) = 3x3y3 - x2y2 + 3/5x3y2
2) a) 5x3 - 5x = 5x( x2 - 1 ) = 5x( x2 - 12 ) = 5x( x - 1 )( x + 1 )
b) 3x2 + 5y - 3xy - 5x = ( 3x2 - 3xy ) + ( 5y - 5x )
= 3x( x - y ) + 5( y - x )
= 3x( x - y ) + 5[ -( x - y ) ]
= 3x( x - y ) - 5( x - y )
= ( 3x - 5 )( x - y )
a: \(=-2x^2y-\dfrac{5}{4}x^2y^2-\dfrac{4}{3}xy^4\)
b: \(=4x^{n-1+n+1}-6x^{n-1+1}=4x^{2n}-6x^n\)
a)\(\left(3x\right)^3-\left(\dfrac{1}{3}\right)^3=\left(3x-\dfrac{1}{3}\right)\left(9x^2+x+\dfrac{1}{9}\right)\)
b)\(x^3-x^2+5x^2-5x-24x+24\)
\(=x^2\left(x-1\right)+5x\left(x-1\right)-24\left(x-1\right)\)
\(=\left(x^2+5x-24\right)\left(x-1\right)\)
\(=\left(x^2+8x-3x-24\right)\left(x-1\right)\)
\(=\left[x\left(x+8\right)-3\left(x+8\right)\right]\left(x-1\right)\)
\(=\left(x-3\right)\left(x+8\right)\left(x-1\right)\)
c)\(x^2+7x+12=x^2+3x+4x+12\)
\(=x\left(x+3\right)+4\left(x+3\right)=\left(x+3\right)\left(x+4\right)\)
d)\(3x^2-3xy-5x+5y\)
\(=3x\left(x-y\right)-5\left(x-y\right)=\left(x-y\right)\left(3x-5\right)\)
\(a,\left(2x-y\right)^2=4x^2-4xy+y^2\)
\(b,\left(5x-7y^2\right).\left(5x+7y^2\right)=\left(25x^2-49y^4\right)\)
\(c,\left(5x-7y\right)^2.\left(5x+7y\right)^2=\left(25x^2-70xy+49x^2\right).\left(25x^2+70xy+49x^2\right)\)
\(d,\left(\frac{1}{3}x+5y\right).\left(5y-\frac{1}{3}x\right)=25y^2-\frac{1}{9}x^2\)
học tốt nha
a) (2x-y)2 = (2x)2 - 2.2x.y + y2 =4x2-4xy+y2
b)(5x-7y2).(5x+7y2) = (5x)2 - (7y2) 2 =25x2 - 49y4
câu c,d mk ko bít làm
3x^2 + 5y - 3xy - 5x
= 3x^2 - 3xy + 5y- 5x
= 3x ( x-y) +5( y-x)
=3x(x-y)- 5( x-y)
= (x-y)(3x-5)
3x^2 + 5y ‐ 3xy ‐ 5x = 3x^2 ‐ 3xy + 5y‐ 5x = 3x ﴾ x‐y﴿ +5﴾ y‐x﴿ =3x﴾x‐y﴿‐ 5﴾ x‐y﴿ = ﴾x‐y﴿﴾3x‐5﴿